Analysis And Mitigation of Harmonics Transformer Distribution at PT. PLN Syiah Kuala - Faisal, Faisal; Lubisa, Ichsan Muhadis; Inayati, Ghina; Tarmizi, Tarmizi (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2024)
Customers receive their electricity from distribution transformers; a disturbance will interfere with this process. High harmonics are typically the source of issues in distribution transformers. The distribution transformer at PT. PLN (Persero) ULP Syiahkuala has two issues: the neutral cable breaking and the main or secondary winding burning. Analyzing harmonics in distribution transformers at PT PLN (Persero) ULP Syiahkuala is the goal of this study. The goal of this study is to measure, examine, and assess the transformers at Syiahkuala ULP in order to select the best mitigation. One transformer's harmonic values were determined by the measurement findings to be out of compliance with requirements, necessitating the use of a variety of passive filters to reduce themThe results of THDi reduction using a passive filter are the values obtained for each phase R, S, and T. These values are in accordance with the established standards. From the results of harmonic mitigation using a passive filter, the results obtained in accordance with the THDv and THDi standards based on IEEE 159-2014 are 8% and 10%, respectively.